Strategi Melakukan Proses Rekrutmen Ditengah Buruknya Citra Perusahaan Pialang - Muhammad Rafif Aledery Wicaksana; Sulastri Irbayuni (Politeknik Kampar, 2023)
This discussion aims to identify and address the challenges faced by brokerage firms in carrying out employee recruitment processes in the context of poor corporate image. Faced with these challenges, the study adopted a crowdsourcing approach by involving brokers and local communities. Methods included surveys, interviews and group discussions with stakeholders. The discussion identified various challenges faced by the Brokerage Company, such as low community trust, lack of interest of prospective employees to join the company, and communication issues. The review recommended various strategies, including efforts to improve the company's image, and more attractive training programs. It also makes an important contribution towards improving the image of brokerage firms and enhancing their recruitment processes. Integrating the brokerage firm into the local community is expected to strengthen the relationship between the firm and the community and create a better recruitment environment. The results of this study are expected to serve as a guide for Brokerage Firms and similar organizations to overcome similar challenges and build better relationships with the community.